AKIBAT HUKUM AKTA PERJANJIAN KREDIT YANG DIBUAT NOTARIS DENGAN JAMINAN HAK TANGGUNGAN ADANYA KEPASTIAN HUKUM DAN KEADILAN PARA PIHAK - Oting Supartini; Anis Mashdurohatun (UNISSULA, 2016)
The purpose of this study is the legal consequences arising out of the Credit Agreement with the guarantee of mortgage studies in case number 127 / Pdt.G / 2014 / PN.SMG, in the District Court of New York, How should a notary to make loan agreement with the Mortgage Guarantee ensure legal certainty.In this study, using juridical empirical method. Type and source of the data used in the primary and secondary data. Collecting data with the study of literature and the (observation, interviews and questionnaires). Analysis of data for qualitative descriptive. As a result of the law on the ratification of the creditors of the credit agreement by notary, with a guarantee of mortgage, based on the wording of Article 6 of Law No. I R 4 Year 1996 on Land and Other Bodies related to the land, the right to sell the object of mortgage on its own power is one embodiment of the priority positions (referent). And as a result of the law of the debtor apply Article 1338 of the Civil Code, Article 1243 applies, Article 1244KUHPerdata, and Article 1237, paragraph (2) of the Civil Code. The legal consequences of Notaries that have fulfilled the provisions of Article 1320 of the Civil Code in accordance with the obligations of and is not in violation of Article 16 on the obligation of, and in compliance with the Article 38, 39, 40 andArticle 44 paragraph (1), (2), (3) and paragraph (4), Law of Republic of Indonesia No. 30 2004 Jo No. 2 Year 2014 concerning Notary and do not violate the code of ethics of the notary, so that the act is still not degraded to act under the hand. Of a credit agreement with a guarantee of mortgage that guarantees the rule of law and justice of the parties, the fulfillment of Article 1320, Article 1321 of the Civil Code, and Notary must comply with Article 15 and Article 16 ofthe Law Notary, implement the Code of conduct and other Law.